2018
DOI: 10.4149/bll_2018_052
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-489 as a biomarker in diagnosis and treatment of cervical cancer

Abstract: miRNA-489 was shown to be a suppressor factor in many cancers, however, evidence on the effects and mechanism of miRNA-489 in progression of cervical cancer is limited. So we aimed to determine the function of miRNA-489 in cervical cancer proliferation and apoptosis in our present study. Interestingly, we found that miRNA-489 was significantly down-regulated in cervical cancer tissues. miRNA-489 overexpression inhibited the cell proliferation and improved the cell apoptosis of cervical cancer cells. Further, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…For instance, miR-338-3p can reduce CC cell growth via regulating MACC1 and MAPK expression [ 24 ]. miR-489 is expressed lowly in CC and reduces the proliferation of CC cells [ 25 ]. miR-221-3p can regulate EMT and metastasis through binding to THBS2 in CC [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-338-3p can reduce CC cell growth via regulating MACC1 and MAPK expression [ 24 ]. miR-489 is expressed lowly in CC and reduces the proliferation of CC cells [ 25 ]. miR-221-3p can regulate EMT and metastasis through binding to THBS2 in CC [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“… 9 A growing body of evidence suggests that the abnormal expression of miRNAs play momentous roles in the tumorigenesis, including CC. 10–12 In this study, using bioinformatics analysis ( http://www.targetscan.org/ ), we found that miR-3150b-3p might bind to TNFRSF11a three prime untranslated region (3’-UTR) to inhibit the expression of TNFRSF11a. Based on the above-mentioned findings, we thus speculated that miR‐3150b-3p via targeting TNFRSF11a inhibited CC development by mediating the p38 MAPK signaling pathway.…”
Section: Introductionmentioning
confidence: 92%
“…In particular, the mutations of PIK3CA E542K and E545K promote glycolysis and proliferation of CC in vitro and vivo [212]. NBPF1, ARHGAP17, miR-99b, -181a2/181b2, -338, -383, -433 and -489, as well as LncRNA ANRIL, CRNDE, NEAT1 and LINC01305 are involved in the proliferation, invasion, autophagy or EMT via PI3K/AKT pathway [213][214][215][216][217][218][219][220][221][222][223][224]. Currently, only preclinical trials of PI3K inhibitor LY294002 has revealed it significantly radiosensitized CC cell lines in vitro and vivo [225,226], and the terminated clinical trials of AKT inhibitor GSK2141795 (NCT01958112, Table 3) has tried to display a novel treatment approach to patients of CC.…”
Section: Nct02240212mentioning
confidence: 99%